2018
DOI: 10.1038/s41598-018-21617-1
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic causes of peripheral intravenous catheter failure based on a parametric computational study

Abstract: Peripheral intravenous catheters (PIVCs) are the most commonly used invasive medical device, yet up to 50% fail. Many pathways to failure are mechanistic and related to fluid mechanics, thus can be investigated using computational fluid dynamics (CFD). Here we used CFD to investigate typical PIVC parameters (infusion rate, catheter size, insertion angle and tip position) and report the hemodynamic environment (wall shear stress (WSS), blood damage, particle residence time and venous stasis volumes) within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
3
46
0
1
Order By: Relevance
“…21 Although it was beyond the scope of this study, this finding does suggest that PIF is associated with other mechanistic causes and is certainly worthy of further investigation. 22 The PIVCs inserted by medical students appear to be a clinician factor associated with PIF. This finding may be relevant to this group's first clinical exposure to PIVC.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although it was beyond the scope of this study, this finding does suggest that PIF is associated with other mechanistic causes and is certainly worthy of further investigation. 22 The PIVCs inserted by medical students appear to be a clinician factor associated with PIF. This finding may be relevant to this group's first clinical exposure to PIVC.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies have indicated a multiple aetiology of phlebitis, as primarily being a physicochemical phenomenon (Maki & Ringer, ; Mestre Roca et al, ). By using computational fluid dynamics (CFD) to report the hemodynamic measure within the vein and catether, Piper et al () established that increasing the infusion flow rate and positioning the catheter tip along the vein wall creates turbulence, that is, stasis that causes vein wall shear stress and phlebitis.…”
Section: Introductionmentioning
confidence: 99%
“…These patients often have limited vascular access. Repeated unsuccessful PIVC attempts cause pain and discomfort for patients (Menegolo et al., ) and are also associated with increased healthcare costs (Tuffaha et al., ) and increased risk of failure (Piper et al., ; Wallis et al., ).…”
Section: Introductionmentioning
confidence: 99%